ELECTRONIC WORD-OF-MOUTH (E-WOM) IN SOCIAL MEDIA AS A PREDICTOR OF INVESTMENT INTENTION IN CAPITAL MARKET - Innayah, Eka Putri; Ekowati, Vivin Maharani; Supriyanto, Achmad Sani; masyhuri, Masyhuri; Johari, Fuadah Binti (Universitas Brawijaya, Indonesia, 2022)
E-WoM1 is vital in generating and creating purchase intentions, so it is significant for use in knowing and analyzing investment intentions. This research aims to analyze and know the effect of Electronic Word-of-Mouth (E-WoM) on investment intention in the capital market with brand dan trust as mediation variables. It belongs to qualitative research with an explanatory research approach. The population of this study refers to the people of Jayapura City. The sampling technique was the purposive sampling technique. The samples in this research are 203 respondents. Questionnaires collected data and analyzed using partial least squares (PLS). The results reveal that E-WoM directly affects brand image and trust. Besides, brand image and trust directly affect investment intention, while E-WoM does not directly affect investment intention. Furthermore, brand image and trust can completely mediate the effect of Electronic Word-of-Mouth (E-WoM) on investment intention and function as full mediation. The findings from this research could be applied to enhance investment intention by building customer trust and sharing the banks' reputation and brand image through E-WoM, so they receive credible information from the bank.